1D and 2D snapping mechanical metamaterials with cylindrical topology. (November 2020) - Yang, Hang; Ma, Li
Abstract: Snapping mechanical metamaterials have garnered significant interest in recent years because of their ability to achieve extremely large strains and shape/configuration changes or recoveries via elastic buckling instability. For 1D snapping 2D periodic structures with planar topological configurations, the snapping mechanisms have been deeply studied. In this article, 1D multistable cylindrical metastructures composed of a periodic arrangement of bistable snapping units with programmable nonlinear mechanical responses are presented. Theoretical analysis, finite element simulations, and experimental verifications are performed to the application for stable and reusable shape-reconfiguration/phase-transformation. Notably, the mechanical characterizations of 2D snapping 2D periodic structures and developed cylindrical configurations are also carried out. The applications for highly stretchable devices and morphable metastructures are proposed. The relationships between geometric parameters as well as the numbers of the unit cells and structure's macroscopic mechanical behavior are concluded. The study significantly expands the ability of snapping metamaterials and opens avenues for the adaptive morphable surfaces as demonstrated by the design of a smart responsive skin that significantly enhances the deformability and programmability.